Melatonin and its receptor MT1 are involved in the downstream reaction to luteinizing hormone and participate in the regulation of luteinization in different species. Issue 3 (1st July 2016) - He, Changjiu; Ma, Teng; Shi, Jianmin; Zhang, Zhenzhen; Wang, Jing; Zhu, Kuanfeng; Li, Yu; Yang, Minghui; Song, Yukun; Liu, Guoshi
Abstract: The functions of melatonin in preovulatory fluid remain elusive. In the current study, we observed that the extremely high level of expression of MT1 in mice granulosa cells was rapidly induced by hCG (equivalent LH) within 2 hours and this was referred as MT1 surge. In cumulus cells, serotonin N‐acetyltransferase (SNAT) was also upregulated by hCG and led to elevated melatonin levels in ovarian follicle fluid. Melatonin application before MT1 surge significantly promoted embryo implantation, and this was probably attributed to a rise in progesterone levels in the serum. The mechanistic studies indicated that melatonin/MT1 (MLT/MT1) signaling remarkably improved the expression of corpus luteum marker genes, that is, Akr1c18 and Cyp11a1 . High‐throughput sequencing results suggested that extracellular matrix (ECM) receptor interaction, focal adhesion, and activation of PI3K/Akt pathway which are involved in granulosa cell luteinization might mediate the actions of MLT/MT1 signal. In addition, this effect on luteinization was compared in different species. It was verified that high melatonin levels exist in serum at estrum of cows and help to improve the first estrus fecundation rate. These results suggested that both melatonin and MT1 are involved in the downstream reaction of hCG (LH) and they play important roles in luteinization. These findings provide the novel information on the physiology of melatonin in animal reproduction.